Statistical Analysis of Agarwood Oil Compounds In Discriminating the Quality of Agarwood Oil - N. S. A., Zubir; M. A., Abas; N., Ismail; Mohd Hezri Fazalul, Rahiman; Saiful Nizam, Tajuddin; M. N., Taib (The Society for Advancement of Science & Technology, 2017)
Agarwood oil is one of the plant’s primary metabolites. Products produced by agarwood oil are very valuable and have a great demand in many fragrance as well as aromatic industries. Enhancing and improving the discrimination technique is the main aim to determine or grade the good quality of agarwood oil. In this paper, all statistical works were performed via SPSS software. Two parameters involved are abundance of compound (%) and quality of the agarwood oil either low or high quality. The result showed that, there is clear significant normality test depends on the parameters through the boxplot and Quantile-Quantile (Q-Q) plot for data distribution. Then, Kolmogorov-Smirnov (K-S), non-parameter test and hypothesis were covered in normality test. The techniques proved their capabilities in statistical analysis for agarwood oil compounds and confirmed that the data is suitable for further work especially for classification.